The Nursing Assessment of Work History in Agricultural Areas with Liver and Kidney Functions in Farmers - Fibriansari, Rizeki Dwi; Maisyaroh, Arista; Widianto, Eko Prasetya (NurseLine Journal; Vol 8 No 1 (2023): May 2023, 2023)
The demand to increase the productivity of agricultural products greatly drives the use of pesticides in agricultural areas. Uncontrolled use of pesticides by farmers and non-compliance with the use of personal protective equipment leads to long-term poisoning that can affect liver and kidney function. However, the relationship between them is poor research. This study aimed to find the relationship between the history of work in agricultural areas with liver and kidney function in farmers. The design of this study was cross-sectional. Respondents for this survey were 36 persons, drawn by purposive sampling. For data, collection questionnaires and interviews are of work history in the agricultural area and observation of laboratory data in the medical records of patients. Data analysis was bivariate analysis with linear regression with p-value <0.05. The normality test with the KolmogorovSmirnov test shows all variables are abnormal distributions (p>0.05). In the analysis with linear regression methods there is a correlation between many pesticides with the value of SGOT (p=0.001) and SGPT (p=0.034), use of PPE with a level of creatinine (p=0.019) and SGOT (p=0.008). Urea has a fairly weak relationship with a work history in the agricultural areas (R=0.157), creatinine has a moderate relationship (R=0.471), SGOT has a weak relationship (R=0.362), and SGPT has a weak relationship (R=0.320). Farmers' local knowledge and wisdom can assist in recognizing and early handling threats due to hazardous materials in the agricultural environment. Therefore, it is necessary to make efforts to minimize the risk of exposure to pesticides, including through the use of personal protective equipment.